2017
DOI: 10.1089/ten.tea.2016.0464
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive Poly(N-vinylcaprolactam) Injectable Hydrogels for Cartilage Tissue Engineering

Abstract: Injectable hydrogels have gained prominence in the field of tissue engineering for minimally invasive delivery of cells for tissue repair and in the filling of irregular defects. However, many injectable hydrogels exhibit long gelation times or are not stable for long periods after injection. To address these concerns, we used thermosensitive poly(N-vinylcaprolactam) (PNVCL) hydrogels due to their cytocompatibility and fast response to temperature stimuli. Changes in the PNVCL molecular weight and concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 62 publications
(88 reference statements)
1
28
0
2
Order By: Relevance
“…Apart from mechanical properties, synthetic polymers can have versatile functions. Poly(N-vinylcaprolactam) (PVCL) is a cytocompatible thermosensitive polymer that can be used to fabricate injectable hydrogels for cartilage tissue engineering [ 42 , 43 ]. Sala et al showed chondrocytes and MSCs exhibited high viability in PVCL hydrogels [ 42 ].…”
Section: Current State-of-art Of Hydrogels Designed For Cartilage Regmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from mechanical properties, synthetic polymers can have versatile functions. Poly(N-vinylcaprolactam) (PVCL) is a cytocompatible thermosensitive polymer that can be used to fabricate injectable hydrogels for cartilage tissue engineering [ 42 , 43 ]. Sala et al showed chondrocytes and MSCs exhibited high viability in PVCL hydrogels [ 42 ].…”
Section: Current State-of-art Of Hydrogels Designed For Cartilage Regmentioning
confidence: 99%
“…Poly(N-vinylcaprolactam) (PVCL) is a cytocompatible thermosensitive polymer that can be used to fabricate injectable hydrogels for cartilage tissue engineering [ 42 , 43 ]. Sala et al showed chondrocytes and MSCs exhibited high viability in PVCL hydrogels [ 42 ]. Both in vitro and in vivo tests showed that cartilage-specific extracellular matrix (ECM) was produced in a chondrocytes-laden PVCL hydrogel.…”
Section: Current State-of-art Of Hydrogels Designed For Cartilage Regmentioning
confidence: 99%
“…The biorthogonal dPGS-PEG hydrogel demonstrated an elastic modulus varying from 1 to 5 kPa by varying the dPGS content and maintained higher cell viability with tissue formation [ 108 ]. PNVCL hydrogels were investigated because of their thermoresponsive in situ gelling properties, showing a LCST value similar to the physiological temperature [ 109 ]. Furthermore, to take advantage of the elastic and biodegradable properties of PEU, hydrogel scaffolds with different pore sizes of 200, 400, and 600 µm and Young’s moduli of 16 ± 3, 7 ± 1, 5.6 ± 0.5 MPa were developed [ 110 ].…”
Section: Hydrogel Composition: Materials Used To Prepare Hydrogelsmentioning
confidence: 99%
“…These macromers are particularly promising for cell encapsulation applications, as they facilitate biointegration and degradation via hydrolysis of the phosphate ester bonds of MAEP. [128] Similar to pNIPAm, are the elastin-like polypeptides (ELPs) with a sol-gel transition at 34 °C, first reported by Urry et al [129] Different cell encapsulation systems using ELPs have been recently described elsewhere. Hydrogels that readily undergo enzymatic degradation have demonstrated improved bone growth and infiltration.…”
Section: Temperature-responsive Cell Encapsulation Systemsmentioning
confidence: 99%